2015
DOI: 10.1093/gerona/glv133
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Adults: A Nationally Representative Profile in the United States

Abstract: Our findings support the importance of frailty in late-life health etiology and potential value of frailty as a marker of risk for adverse health outcomes and as a means of identifying opportunities for intervention in clinical practice and public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
462
14
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(515 citation statements)
references
References 27 publications
25
462
14
14
Order By: Relevance
“…A new study conducted by Tan et al demonstrated that frailty is associated with a higher number of falls and falls with serious consequences (36). Bandeen et al determined that the incidence of falls in the past year was 30.5% in the robust population, 32.9% in prefrail patients, and 54.9% in frail patients (25). A metaanalysis carried out recently by Kojima et al demonstrated that male, frail, community-dwelling older adults are subject to higher fall risks (23).…”
Section: Discussionmentioning
confidence: 99%
“…A new study conducted by Tan et al demonstrated that frailty is associated with a higher number of falls and falls with serious consequences (36). Bandeen et al determined that the incidence of falls in the past year was 30.5% in the robust population, 32.9% in prefrail patients, and 54.9% in frail patients (25). A metaanalysis carried out recently by Kojima et al demonstrated that male, frail, community-dwelling older adults are subject to higher fall risks (23).…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in the USA with 7.439 elderly aged 65 or older found a 15% prevalence of frailty, and the main risk factors were: advanced age, female sex, low income, racial/ethnic minorities and the presence of multiple chronic diseases (8) .…”
Section: Introductionmentioning
confidence: 99%
“…1 National data from the United States suggest that 15% of community-dwelling persons aged 65 years or older are frail and 45% are prefrail. 2 The high prevalence of frailty is a significant public health problem. The older adult population is growing, and frailty is associated with increased risk of disability, hospitalization, and mortality.…”
mentioning
confidence: 99%